The Inter-Institutional Consortium (I-IC) processing center, 1981-1991 a performance audit - Garcia, Perla T. (1993)
This study determined the efficiency and effectiveness of the Inter-Institutional Consortium (I-IC) Processing Center in its ten years of operation, (1981-1991), in terms of its implementing processes and products within its context and input components. The I-IC Processing Center is a cooperative centralized cataloging project of libraries of five institutions of higher learning, namely: De La Salle University, St. Paul College, Manila, and St. Scholastica's College.